Urban responses to restrictive conservation policy during drought. Issue 5 (31st May 2017) - Palazzo, Joseph; Liu, Owen R.; Stillinger, Timbo; Song, Runsheng; Wang, Ying; Hiroyasu, Elizabeth H. T.; Zenteno, Jose; Anderson, Sarah; Tague, Christina
Abstract: With climate change, the extent, severity, and frequency of droughts around the world are expected to increase. This study analyzed the ability of water districts to meet mandatory urban water conservation targets, which are a common policy response to drought. During California's recent record‐breaking drought, a 25% state‐wide use reduction objective was set and met. However, only 50% of urban water districts analyzed in this study reached their individual conservation target, which offers an opportunity to evaluate the factors associated with successful water use reduction. The findings show that the inclusion of water districts in the polycentric import structure may improve water conservation, but that source diversity may offer water districts a perceived buffer from the need for immediate water use reductions. Drought severity and lower median incomes are associated with greater water conservation, and conservation varies by hydrologic region. This analysis offers insights into institutional design and suggests that local biophysical and economic conditions shape responses in systematic ways that should be addressed by public policy responses to drought. Plain Language Summary: Mandatory water conservation is a common response to drought in urban areas. California's recent record‐breaking drought resulted in a statewide policy adopting this strategy. The response was stronger in some areas than others, and this research predicts responses using characteristics of urban water districts. These include economic, environmental and institutional factors. We find that coordination between water districts helps achieve greater conservation, and that awareness of local conditions is a key driver of water use reduction. Key Points: A database of urban water districts in California was constructed and analyzed to investigate the factors associated with successful water use reduction Districts increased conservation relative to targets if they imported water, experienced more severe drought, or had lower median incomes Drought policy should be sensitive to local economic and biophysical conditions and water managers should consider adopting polycentric structures